Outcome of Arterio-Venous Fistula With and Without Central Venous Catheter in Patients with End Stage Renal Disease (Mugda Medical College Journal, 2025)
End stage renal disease (ESRD) patients often need to secure a vascular access for haemodialysis and arterio-venous fistula (AVF) is intended to serve the purpose. However, an AV fistula needs at least 4-6 weeks to get anatomically set and physiologically functional. We observe that a good number of patients undergo haemodialysis by central venous catheter (CVC) before securing an AV fistula. This cross-sectional, descriptive study was conducted among 80 patients of ESRD referred to the Department of Surgery, Sylhet MAG Osmani Medical College Hospital, Bangladesh, between January and June of 2016, to compare early outcome of arterio-venous fistula with and without central venous catheter. Patients having AV fistula with CVC were enrolled in group A (n=40), and patients without CVC were in group B (n=40). The mean age was 59.25±10.95 years in group A and 60.62±10.35 years in group B. A male predominance was observed; male-female ratio was 3.44:1. During follow-up visits, adverse events like erythema, haematoma formation, serous or serosanguinous discharge were found less in group B compared to group A. Among complications, wound infection, pseudoaneurysm, stenosis and total fistula failure (within three months) was observed less in group B. Our study demonstrated that patients having arterio-venous fistula without central venous catheter had better outcome along with less complications than those had A-V fistula with central venous catheter. Hence, A-V fistula first strategy can be implemented with low morbidity in ESRD patients.Mugda Med Coll J. 2025; 8(2): 118-124